The Monetization of Misogyny: Platform Capitalism and Manosphere's Political Economy - Annisa Nadhifa Ramadhani (Jurnal Dinamika Global, 2026)
Contemporary research often views the Manosphere as a cultural backlash or a masculinity crisis. This study reinterprets it as a political and economic system rooted in platform capitalism. Using International Political Economy, it explores how algorithms, affiliate marketing, and multi-level marketing profit from misogynistic radicalization. The analysis of Andrew Tate's "Hustler's University" shows that radicalization does not result from failed content moderation but is a predictable outcome of profit-driven algorithmic systems. Followers become unpaid digital workers, turning ideology into paid labor. The study argues that global governance and counter-terrorism strategies do not adequately address the issue. They focus on removing content instead of disrupting revenue streams. This changes the approach to platform regulation, shifting from speech-based moderation to financial de-platforming and algorithmic auditing.